Enrichment of CD44 in Exosomes From Breast Cancer Cells Treated With Doxorubicin Promotes Chemoresistance - Wang, Xiaohong; Cheng, Kai; Zhang, Guoqiang; Jia, Zhongming; Yu, Yue; Guo, Jiwei; Hua, Yitong; Guo, Fengli; Li, Xiaoqiang; Zou, Weiwei; Sun, Hongguang; Dong, Jianli; et al. (Frontiers in Oncology, 2020)
Exosomes have been shown to be associated with chemotherapy resistance transmission between cancer cells. However, the cargo and function of exosomes changed in response to doxorubicin(DOX) remains unclear. We compared proteome profiles of exosomes extracted from the supernatant of MCF-7(S/Exo) and MCF-7/ADR(A/Exo) cells. We confirmed the differential expression of the candidate target-exosomic-CD44 by immune gold staining and western blot. We further studied the changes of chemosensitivity and CD44 expression in MCF-7 cells co-incubated with A/Exo. We analyzed the levels of exosomal CD44 from patient plasma, then compared the sensitivity and specificity of exosomic CD44 and plasma CD44 on diagnosis of chemoresistance. We modified the MCF-7-derived exosomes loaded with siRNA against CD44 to observe the effects of targeting reduced CD44 expression in lumimal A breast cancer cells. We found that DOX increased the exosomes release from MCF-7/ADR cells and the exosomes mediated proteins intercellular transfer in breast cancer chemoresistance regulation. The candidate target of CD44 in A/Exo was much higher than in S/Exo and the increase levels of exosomic CD44 (21.65-fold) was much higher than cellular CD44(6.55-fold). The same results were obtained in clinical samples. Exosome-siRNA targeted CD44 (Exos-siCD44) could efficiently targeted to silence its expression. When co-cultured on Exos-siCD44, breast cancer cells exhibited reduced cell proliferation and enhanced susceptibility to DOX and the same phenomenon was observed in mice. Drug-resistant breast cancer cells spread resistance capacity to sensitive ones by releasing exosomes and that such effects could be partly attributed to the intercellular transfer of proteins especially CD44.